Implementation of Problem-Solving Model with The Redox Booklet to Enhance Problem-Solving Skills - Jeanette Valentine Rut Tewal; Eny Enawaty; Husna Amalya Melati (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
This study aimed to increase students' problem-solving skills through problem-solving learning with a booklet on the concept of reduction and oxidation reactions. This research used the pre-experimental method with a one-group pretest-postest design which was conducted in SMAN 5 Pontianak. Participants consist of 37 students of tenth-grade (Class IPA 4). The research instrument was used containing two valid and reliable essay questions. Data analyst was done descriptively and statistically, including n-gain and Wilcoxon test. Students' problem-solving skills were measured before and after being given treatment. The research results showed that the N-Gain (0,62) value with medium category of students problem-solving skills. These results were supported with the Wilcoxon test obtaining a significance value of 0,00 (<0,05). It indicated that H0 was rejected dan H1 was accepted. These results indicated the problem-solving learning model with a booklet could improve students' problem-solving skills on reduction and oxidation reaction material.